Abundance, damage severity and management of guava mealybug, ferrisia virgata ckll (SAARC Journal of Agriculture, 2019)
The research was carried out to know the abundance and damage severity of mealybug on sarupkathi variety of guava and to evaluate the efficacy of jet powder and Fighter 2.5EC for suppressing populations of mealybug during January to October 2014. Results revealed that the highest number of guava mealybug was observed on middle leaf (42/leaf) while the lowest number was on lower leaf (13/leaf). The highest percent leaf area covered by mealybug was found on middle leaf (78%) while the lowest was on fruit (18%). Maximum temperature and relative humidity had a positive correlation on the mealybug population while the rainfall showed a negative correlation. The highest percent mortality was observed in T2 treatment (Jet powder applied @ 5.0 g L-1 of water) at 24 HAT (hours after treatment) (86.05%) and 48 HAT (93.83%), respectively. At 72 HAT, the highest percent mortality was observed T3 treatment (Jet powder applied @ 7.5 g L-1 of water). In case of insecticidal control, the highest percent mortality was observed in T2 (100%) and T3 (100%) treatments, respectively followed by T1 (98.03%) at 24 HAT. Similar trends were also observed among all treatments at 48 HAT and 72 HAT, respectively. No significant differences were found among three doses of Fighter 2.5EC. The lowest percent mortality of mealybug population was found in T4 (Water spray forcibly) at 24 HAT, 48 HAT and 72 HAT, respectively. No mortality was recorded in untreated control at different HAT in both application of soap solution and insecticides.SAARC J. Agri., 16(2): 73-82 (2018)